Hydrogel‐Enabled Transfer Printing: Hydrogel‐Enabled Transfer‐Printing of Conducting Polymer Films for Soft Organic Bioelectronics (Adv. Funct. Mater. 6/2020). (5th February 2020) - Zhang, Shiming; Ling, Haonan; Chen, Yihang; Cui, Qingyu; Ni, Jiahua; Wang, Xiaochen; Hartel, Martin C.; Meng, Xiang; Lee, KangJu; Lee, Junmin; Sun, Wujin; Lin, Haisong; et al.
Abstract : Patterning of conducting polymer poly(3, 4)ethylenedioxythiophene doped with polystyrene sulfonate (PEDOT:PSS) thin films directly on hydrophobic soft substrates is challenging. Shiming Zhang, Ali Khademhosseini, and co‐workers, in article number 1906016, report that hydrogels are capable of transfer‐printing patterned PEDOT:PSS thin films from glass onto various soft substrates. Using this method, skin‐attachable organic electrochemical transistors are developed for personalized biosensing applications.